A Study of the Effect of Yoga on Weight and Body Mass Index of Obese Girls Students - Mr. Siddharth Balesha (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
The purpose of this research study was to study the effect of yoga on weight and body mass index of obese student sisters. For this research study female students of Madhav University,Pindwara, Rajasthan were selected as subjects by random method. In this research study 30 female students were divided into two groups namely yoga training group and 30 female students as control group. Female students in the age group of 18 to 25 years were selected in this research study. Which was verified from the college records. Standard of measurement was height measurement by stadiometer and weight and body mass index by body composition machine. The score obtained through the test of this research study was tested for significance at 0.05 level by applying 't' ratio to check the statistical significance in the statistical analysis. The findings of which were seen as follows. Six weeks of yoga showed no significant difference in subjects' weight. Six weeks of yoga showed no significant difference in subjects' body mass index (B.M.I.).